2021
DOI: 10.1098/rsif.2021.0050
|View full text |Cite
|
Sign up to set email alerts
|

How the replacement of cholesterol by 25-hydroxycholesterol affects the interactions with sphingolipids: The Langmuir Monolayer Study complemented with theoretical calculations

Abstract: In this paper, a representative of chain-oxidized sterols, 25-hydroxycholesterol (25-OH), has been studied in Langmuir monolayers mixed with the sphingolipids sphingomyelin (SM) and ganglioside (GM 1 ) to build lipid rafts. A classical Langmuir monolayer approach based on thermodynamic analysis of interactions was complemented with microscopic visualization of films (Brewster angle microscopy), surface-sensitive spectroscopy (polarization modulation–infrared reflection–absorption spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 60 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…This suggested that these two lipids had a strong affinity for each other. Indeed, further studies on interactions in two-component systems confirmed strong affinity of cholesterol to sphingolipids (mainly sphingomyelin and gangliosides [ 78 , 79 ]), which may be explained on the basis of the molecular geometry [ 80 , 81 ]. Specifically, the inverted cone shape of cholesterol (promoting negative curvature structures) fits perfectly with the truncated cone-like shape of sphingomyelin or cone-shape of ganglioside GM 1 (both forming positive curvature structures) [ 81 ].…”
Section: Interactions In Multi-component Biomimetic Systemsmentioning
confidence: 99%
See 3 more Smart Citations
“…This suggested that these two lipids had a strong affinity for each other. Indeed, further studies on interactions in two-component systems confirmed strong affinity of cholesterol to sphingolipids (mainly sphingomyelin and gangliosides [ 78 , 79 ]), which may be explained on the basis of the molecular geometry [ 80 , 81 ]. Specifically, the inverted cone shape of cholesterol (promoting negative curvature structures) fits perfectly with the truncated cone-like shape of sphingomyelin or cone-shape of ganglioside GM 1 (both forming positive curvature structures) [ 81 ].…”
Section: Interactions In Multi-component Biomimetic Systemsmentioning
confidence: 99%
“…Therefore, these mixtures can be considered as artificial lipid rafts, among which the SM/Chol system is used as the simplest model [ 78 , 82 85 ].
Figure 2 Δ G exc plots for: ( a ) cholesterol/sphingomyelin and ( b ) cholesterol/ganglioside mixtures (modified from [ 78 , 79 ] with permission from Elsevier and the Royal Society Publishing.
…”
Section: Interactions In Multi-component Biomimetic Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies of the properties of raft-forming lipids in Langmuir monolayers show that 25-HC interacts more strongly than cholesterol with sphingomyelin and slightly less strongly with ganglioside GM1. Therefore, 25-HC can participate in the formation of lipid rafts and even displace cholesterol from them [113]. Indeed, the addition of 25-HC to the artifi cial bilayer membrane composed of a mixture of cholesterol and 1-palmitoyl-2-oleoylphosphatidylcholine leads to a shift of cholesterol towards the water surface and increase in its accessibility to external acceptors; which reduces the ability of cholesterol to condense the lipid bilayer [114].…”
Section: Hydroxycholesterol As a Molecule Of Intercellular Interacti...mentioning
confidence: 99%